EFFECT OF «TREAT-TO-TARGET» ANTIRHEUMATIC THERAPY ON DIASTOLIC DYSFUNCTION OF THE LEFT AND RIGHT VENTRICLES IN PATIENTS WITH EARLY RHEUMATOID ARTHRITIS DURING 18 MONTHS OF OBSERVATION - I. G. Kirillova; D. S. Novikova; T. V. Popkova; Yu. N. Gorbunova; E. I. Markelova; Yu. O. Korsakova; O. A. Fomicheva; A. V. Volkov; E. L. Luchikhina; N. V. Demidova; K. A. Kasumova; S. A. Vladimirov; et al. (Рациональная фармакотерапия в кардиологии, 2015)
Aim. To study the effect of «treat-to-target» antirheumatic therapy on diastolic dysfunction of the left (DDLV) and right (DDLV) ventricles in patients with early rheumatoid arthritis (RA) during 18 months of observation. Material and methods. The study included patients with early RA (n=66; 71% women; age - 56 [46; 61] years) with moderate/high activity (DAS28 5.3 [5.0; 6.2]), seropositive on rheumatoid factor (77%) and/or cyclic citrullinated peptide antibodies (100%), disease modifying anti-rheumatic drugs (DMARD) and glucocorticoids naive. Treatment with methotrexate (MTX) with the escalation of the dose up to 25-30 mg/week subcutaneously was initiated in all the patients. After 3 months in 47 (71%) patients biologics were added to MTX due to its inefficiency. In 18 months remission of RA was achieved in 44% of the patients. 51 (77%) patients had a cardioprotective therapy. The target blood pressure (BP) level was achieved in 38 (58%) patients. Evaluation of traditional cardiovascular risk factors, 24-hour BP monitoring and echocardiography were performed in all patients initially and in 18 months of MTX/MTX + biologics use. Results. After 18 months DDLV incidence decreased by 7% (from 49% to 42%; p>0.05) and DDRV incidence decreased by 5% (from 24% to 17%; p>0.05). A more significant decrease in DDLV incidence [from 23 (62%) to 18 (49%)] and of DDRV incidence (from 12 (32%) to 6 (16%)] (р=0.05), was found in MTX + biologics group than in MTX only group [DDLV incidence remained unchanged - 7 (28%), and DDRV incidence increased from 3(12%) to 4 (16%); p>0.05]. The normalization of left ventricle (LV) diastolic function in early RA patients depended primarily on the efficacy of antihypertensive treatment, and of right ventricle (RV) diastolic function - on the achievement of target BP level and RA remission. Reduced erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) plasma levels were associated with the improved LV diastolic function [E/A LV and ΔESR (r=-0,3; p<0,04), E/A LV and CRP (r=-0,2; p<0.05), A LV and ESR (r=0.3; p<0.01)] and improved RV diastolic function [ΔA RV and ΔCRP (r=0.4; p<0.003), ΔE RV and ΔCRP (r=0.3; p<0.01), E/A RV and DAS28 (r=-0.5; p<0.001), E/A RV and CRP (r=-0,3; p<0.05)] by the 18th month of the study. Conclusion. In early RA patients after 18 months the downward trend of DDLV incidence and a significant reduction of DDRV incidence were found, more expressed in patients treated with MTX + biologics. The achievement of RA remission and target BP level is a prerequisite for the normalization of LV and RV diastolic function and slowing the progression of heart failure.